A Proposal in Strengthening 5 Elements of Corporate Value, through Cultural and Transformational Leadership Programs As an effort in succeeding transformation at PT. Kereta Api Indonesia (Persero) - Ramadhani, Tisya Andriana; Bangun, Yuni Ros (The Indonesian Journal of Business Administration, 2012)
PT. Kereta Api Indonesia (Persero) or Indonesian Â Railway Enterprise is an Indonesian State Owned Company which provides railway transportation for both,passengers and goods, which is currently transforming to become more customer driven. Â To support this intention, a new organization Â culture consisting Â of five values (integrity,Â professional, safety, innovation, service excellence) is introduced.Â Â Therefore, a research was conducted to help identify â€œkey driversâ€ which could enhance the implementation Â of these five values.Â Â Organizational Â culture traits, which consist of adaptability, involvement, mision, and consistency; and transformational leadership, consisting of idealized behavior, idealized attribute,Â inspirational Â motivation, individualized Â consideration, Â and intellectual stimulation Â were chosen as the observedÂ variables that will be tested towards Â these five values.Â Â Result showed Â that these two variables does have a meaningful relationship towards the organizationâ€™s five values. From a more in-depth finding, it was then determined that mission, adaptability, involvement (from cultural traits) serves as a key driver which enhance Â theÂ organizationâ€™s Â five values.While Â inspirational Â motivation (from transformationalÂ leadership), serves as a key driver in enhancing the implementation Â of organization culture Keyword:Â Indonesian Railway Enterprise, Corporate Value, Organization culture, Transformational leadership